Automated Low Cost Method of Quantification of Hepatitis C Virus (Bangladesh Journal of Medical Science, 2015)
This paper describes the development of a Dig-dUTP based multiplex real time RT-PCR for the simultaneous detection of HCV viral amount in plasma samples. Viral genomes were identified in the same sample by Dig-dUTP PCR 216 bp region. Analysis of known scalar concentrations of reference plasma indicated that the multiplex procedure detects at least 500 copies/ml of HCV. In addition, we also assayed HCV viral load in eighty co-infected patients and in fifteen blood donors, confirming the sensitivity and specificity of the assay. This method may represent a useful alternative method for the detection of HCV co-infection, reliable for a rapid and relatively inexpensive screening of blood donors. The assay may be used to determine post-therapy viral clearance.Bangladesh Journal of Medical Science Vol.14(3) 2015 p.247-253